Exploring the relations between social support and social identity in adolescent male athletes - Bruner, M. W.; McLaren, C.; Swann, C.; Schweickle, M. J.; Miller, A.; Benson, A.; Gardner, A.; Sutcliffe, J.; Vella, S. A. (Research Quarterly for Exercise and Sport, 2021)
Purpose: Social identity (i.e., the strength with which individuals identify with a group) is a key mechanism through which youth sport participants derive developmental benefits. However, despite the importance of one`s social identity in promoting these benefits, our understanding of the correlates of social identity within the sport context is limited by the absence of evidence. To address this gap, this study investigated the relations between perceived social support from coaches, family, and friends and social identification. Method: Male adolescent athletes (N = 344) completed measures of social support and social identity as part of a cross-sectional design. Latent profile analysis was used to identify distinct social support profiles. Results: Four latent profiles were identified: higher support, average support, diminished support, and lower support. ANCOVA results indicated that profile membership corresponded to significant differences in social identity perceptions, p < .001, partial n² = .26. Participants in the higher social support profile perceived significantly higher social identity when compared with profiles of average, diminished, and lower support (ps < .05, Cohen`s d =.67). Conclusion: Results highlight the association between support from different social agents and social identity in youth sport. Better understanding the correlates of social identity may be critical in enhancing the developmental benefits of participation in organized team sports given the relationship with social identity.